2015
DOI: 10.1016/j.neulet.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for sustained cortical involvement in peripheral stretch reflex during the full long latency reflex period

Abstract: Adaptation of reflexes to environment and task at hand is a key mechanism in optimal motor control, possibly regulated by the cortex. In order to locate the corticospinal integration, i.e. spinal or supraspinal, and to study the critical temporal window of reflex adaptation, we combined transcranial magnetic stimulation (TMS) and upper extremity muscle stretch reflexes at high temporal precision. In twelve participants (age 49 ± 13 years, eight male), afferent signals were evoked by 40 ms ramp and subsequent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The short-latency stretch response depends on the stretch velocity and involves a spinal network (Houk et al, 1981 ). The time delays in the afferent pathway from the periphery to the brain (20–30 ms) (MacKinnon et al, 2000 ) and the efferent pathway from the brain to the periphery (~20 ms) (Perenboom et al, 2015 ) would not allow for a transcortical pathway in the short-latency stretch response. Several experimental studies indicated cortical contributions to the long-latency stretch response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-latency stretch response depends on the stretch velocity and involves a spinal network (Houk et al, 1981 ). The time delays in the afferent pathway from the periphery to the brain (20–30 ms) (MacKinnon et al, 2000 ) and the efferent pathway from the brain to the periphery (~20 ms) (Perenboom et al, 2015 ) would not allow for a transcortical pathway in the short-latency stretch response. Several experimental studies indicated cortical contributions to the long-latency stretch response.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings from cortico-motoneuronal cells in Macaque monkeys showed a cortical effect on the long-latency stretch response (Cheney and Fetz, 1984 ). Subthreshold transcranial magnetic stimulation (TMS) over the contralateral motor cortex can modulate the long-latency stretch response but not the short-latency stretch response (Perenboom et al, 2015 ). Recent studies indicate the long-latency stretch response is not as simple as a “reflex” and at least could partly involve a voluntary feedback control component (Pruszynski et al, 2011 ; Pruszynski and Scott, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…What is the substrate of this modulation and how does it work out in a functional way? Experiments identified the long latency reflex as the primary carrier of modulatory action (Pruszynski and Scott, 2012 ) as it was found to be dependent on instruction (Rothwell et al, 1980 ; Krutky et al, 2010 ), pharmacological agents like Tizanidine (Meskers et al, 2010 ), Transcranial Magnetic Stimulation (TMS; van Doornik et al, 2004 ; Pruszynski et al, 2011 ; Perenboom et al, 2015 ), task (Hallett et al, 1981 ) and scaled to task related urgency (Crevecoeur et al, 2013 ). According to optimal control theory, reflexes are adapted continuously and instantaneously based on manipulation of sensory information during voluntary movement (Pruszynski and Scott, 2012 ).…”
Section: The Nervous System: Afferent Feedback Modulation and Supraspmentioning
confidence: 99%
“…According to optimal control theory, reflexes are adapted continuously and instantaneously based on manipulation of sensory information during voluntary movement (Pruszynski and Scott, 2012 ). Evidence for cortical involvement in the long latency reflex period is ample; whether modulation is located spinally of cortically is yet unknown (Figure 2 , Perenboom et al, 2015 ).…”
Section: The Nervous System: Afferent Feedback Modulation and Supraspmentioning
confidence: 99%
“…This reaction of removing your hand very quickly is a natural response within your body, designed to protect you [1]. This quick response is called a reflex, and reflexes occur without conscious thinking or planning, meaning the brain is not involved in them.…”
mentioning
confidence: 99%